Implementasi program psycologycal support dalam pengembangan kemandirian kelompok difabel cirebon - Widiyanti, Purwita; Suryadi (Fakultas Ilmu Sosial dan Ilmu Politik - Universitas Garut, 2025)
This research aims to determine the effectiveness of implementation psychological support in increasing the independence of disabled people in Lemahabang District. Approach psychological support includes peer counseling, motivation and mentoring activities focused on mentally and emotionally strengthening people with disabilities. Through participatory methods and continuous mentoring, this program has succeeded in increasing self-confidence, understanding of one's potential, and ability to adapt to everyday life. The research results show that psychological support plays an important role in encouraging the independence of people with disabilities, both in the social aspect. Apart from that, family and community involvement is a supporting factor for the success of this program. The recommendation from this research is the need for program sustainability through collaboration between the government, social institutions, as well as strengthening aspects of economic empowerment as a more comprehensive effort to support independence.